STRATEGI HRM DALAM MENCIPTAKAN KOMITMEN DAN RETENSI MENUJU GOING CONCERN PERUSAHAAN - Suhardoyo Suhardoyo (Universitas Bina Sarana Informatika, 2020)
Currently, employee commitment and retention have become an important strategic aspect for the organization. It is not only important to have the best and talented employees and have the commitment to need to maintain it for long-term benefits for both the organization and society in general. Sehinnga needs to be explored various factors that can increase retention and commitment for employees as a strategy that can be pursued by HRM that needs to be implemented. Based on the results of the study can be examined findings as factors that influence employee commitment and retention in the work environment that affect the going concern of the organization. This study examines the following factors career development opportunities, talent management strategies, recruitment, onboarding and orientation, investment in training and development, compensation and benefits, work-life balance, leadership, career development path. There is no fixed practice by a company that shows important things to an organization. But essentially every different organization will give different emphasis depending on compliance with organizational conditions that can foster retention and commitment. It is hoped that organizational understanding can be taken which provides a holistic view of the various practices that the organization must adapt to maintain high levels of employee retention and commitment to maintaining the organization's life